DC-SIGN expression on podocytes and its role in inflammatory immune response of lupus nephritis. (24th November 2015) - Cai, Minchao; Zhou, Tong; Wang, Xuan; Shang, Minghua; Zhang, Yueyue; Luo, Maocai; Xu, Chundi; Yuan, Weijie
Summary: Podocytes, the main target of immune complex, participate actively in the development of glomerular injury as immune cells. Dendritic cell-specific intercellular adhesion molecule-3-grabbing non-integrin (DC-SIGN) is an innate immune molecular that has an immune recognition function, and is involved in mediation of cell adhesion and immunoregulation. Here we explored the expression of DC-SIGN on podocytes and its role in immune and inflammatory responses in lupus nephritis (LN). Expression of DC-SIGN and immunoglobulin (Ig)G1 was observed in glomeruli of LN patients. DC-SIGN was co-expressed with nephrin on podocytes. Accompanied by increased proteinuria of LN mice, DC-SIGN and IgG1 expressions were observed in the glomeruli from 20 weeks, and the renal function deteriorated up to 24 weeks. Mice with anti-DC-SIGN antibody showed reduced proteinuria and remission of renal function. After the podocytes were stimulated by serum of LN mice in vitro, the expression of DC-SIGN, major histocompatibility complex (MHC) class II and CD80 was up-regulated, stimulation of T cell proliferation was enhanced and the interferon (IFN)-γ/interleukin (IL)-4 ratio increased. However, anti-DC-SIGN antibody treatment reversed these events. These results suggested that podocytes in LN can exert DC-like function through their expression of DC-SIGN, which may be involved in immune and inflammatory responses of renal tissues. However, blockage of DC-SIGN can inhibit immune functions of podocytes, which may have preventive and therapeutic effects.